Tragic Maladaptation. The Case of Nina Petrovskaya - Bielniak, Nel (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
Nina Petrovskaya (1879–1928) went down in history as a muse for Russian symbolists and a heroine of stormy affairs, which obscured her creative activity. Her inability to adapt to the social requirements intensified during emigration. As a poor foreigner with introverted tendencies, remaining outside the labor market for a long time and addicted to psychoactive substances, she was unable to adapt to the new realities and was exposed to exclusion. A difficult social and living situation and intensifying depressive states accompanied her in Rome, Berlin and Paris. Interestingly, Petrovskaya remained not only on the margins of social life in the host countries, but also of the Russian diaspora. She left her homeland at the end of 1911 with the intention of staying abroad forever. In the fall of 1922 in Berlin, her fate came into contact with that of the representatives of the so-called the first wave of emigration, including many of her friends. However, time and living for over a decade in a different sociopolitical reality made her unable to communicate with them. All this was recorded in her correspondence from 1919–1925 to her fellow countryman Olga Resnevič-Signorelli, whom she met in Italy, and from 1927–1928 to the literary critic Yuly Aykhenvald.